Niveles séricos de glucosa en pescadores artesanales de Huanchaco y sus familiares. marzo 2008 - Quiroz Morales, Christian Carlos (2008)
Study the serum glucose levels in artisan fishermen of Huanchaco and their relatives. The amount of analyzed samples was 85 of which 23 correspond to artisan fishermen and 62 to its relatives. These were analyzed by the biochemical method of the Glucose oxidase/peroxidase being that the greater percentage of samples is within the normal values of glucose. Also the age of greater incidence in presenting/displaying hiperglicemy this between 35 and 65 years, being this one for both sexes. It is important to stress that the habitual consumption of fish in its daily diet has allowed to maintain the sanguineous glucose levels within the normal limits in the great percentage of this population. With it we can demonstrate the importance of essential oils Omega 3 and 6 in the prevention of chronic diseases like the Mellitus Diabetes